The study of band structure of graphite intercalation compound containing sodium calculated using density functional theory - Ahmad Nazrul Rosli; Wahab I.F.; Zabidi N.A.; Kassim H.A. (Institute of Physics Publishing, 2024)
Indexed by WOS/ Scopus